The Evolving Domestic and International Law Against Foreign Corruption: Some New and Old Dilemmas Facing the International Lawyer - Juscelino F. Colares (Washington University Global Studies Law Review, 2006)
For over two decades, the Foreign Corrupt Practices Act (“FCPA”) and, more recently, the Organization for Economic Cooperation and Development Convention on Combating Bribery of Foreign Public Officials in International Business Transactions (“OECD Convention”) have delineated to U.S. lawyers and their clients which international transactions are proscribed and punished as corrupt. However, like any other statute, the FCPA and the OECD Convention are unable to cover all the permutations of activity that would seemingly constitute transnational corruption. This Article explores what is prohibited and permissible under the FCPA and the OECD Convention, highlighting the tension between operating outside the coverage of these legal precepts while still complying with the rules of professional conduct. It concludes by demonstrating, by means of various scenarios, that there is no substitute for a lawyer's reliance on her professional and ethical judgment. Reprinted by permission of the publisher.
Keywords: International business enterprises -- Law & legislation; Corruption -- Law & legislation; Legal ethics